Gambaran Konsep Diri dan Kecemasan pada Orang Tua yang Memiliki Anak Retardasi Mental di Sekolah Luar Biasa B-C Kurnia Kabupaten Garut - Lusi Aprianti; Ali Mustofa; Cucu Rokayah (stikes dharma husada bandung, 2018)
Mental retardation is a weakness of mind with intelligence less than period of development from birth, children with mental retardation need more attention and support from parents, because children with mental retardation have a high degree of dependence on parents to meet their needs, whereas happen to parents who have children with mental retardation increased burden on parent, it could trigger emergence of psychosocial problems such change self concept and anxiety. This research conducted to determine the self concept and anxiety in parents who have children with mental retardation in Special School B-C Kurnia Garut. . This research use quantitative descriptive method with cross sectional approach, population in this research 54 with total sampling technique, instrument used in form of self concept questionnaire that has been standardized with validity test value 0,66 and Dass anxiety questionnaire. The results showed that 70.9% of parents have positive self-concept and 45.5% of parents have moderate anxiety. The conclusion of this research is that parents who have children with mental retardation have positive self-concept and have moderate anxiety. Suggestions for parents who experience moderate anxiety levels that health workers should provide motivation and information in the form of counseling about the children mental retardation health and expected to family members could provide more support and attention to parents who have children with mental retardation.